The Influence of Food Availability and Food Access on Food Security among Poor Households in Baturaja City - Erni Efriyani; Munajat Munajat; Yetty Oktarina (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Food is a fundamental human right guaranteed by the 1945 Constitution. Although South Sumatra is a major rice producer, Ogan Komering Ulu (OKU) Regency still faces nutritional and poverty challenges, with a Desirable Dietary Pattern (DDP) score of 88.4, which remains below the ideal national standard of 100. This study aims to analyze the influence of food availability and food access on the food security of poor households in OKU Regency. Using a quantitative survey method with 100 respondents, data were analyzed using multiple linear regression. The results indicate that both food availability and food access have a positive and significant influence on the food security of poor households, with food access providing a greater contribution.